EFFECT OF ADDITION COW MANURE AND SPRAYING WITH TRIACONTANOL ON THE GROWTH AND YIELD OF OLIVE TREES CV. KHASTAWI - A. F. Shafeeq; N. T. Abd; R. M. Hamad; M. A. Oudah (مجلة الأنبار للعلوم الزراعية)
Olive trees suffer from many problems, the most prominent of which is low yield and alternating fruiting due to poor nutrition and environmental problems such as high temperatures and intense solar radiation. This study occurred in a private olive orchard within the Ramadi Jazeera area through 2022 growth phase for assessing their impacts when adding cow manure at levels of (0, 5, 10 kg tree-1) and applying the growth regulator Triacontanol using levels containing (0, 10, 20 mg L-1) on the growth as well as yield of 12-year-old Khastawi olive trees. The experiment used a factorial design with two components based on the Randomized Complete Block Design (RCBD) and included three replicates. Findings indicated the significant advantage for the therapy involving the addition of cow manure at a rate of 10 kg per tree in terms of branch length increment, leaf count increase area of leaves, proportion of dry substance within leaves, chlorophyll concentration in leaves, carbohydrate content in branches, fruit shape parameters, average fruit weight, total yield, dry matter percentage in fruits, and oil content estimation.  When growth regulators were used along with Triacontanol spraying with amount of 20 mg L⁻1, there had been a noticeable increase within branch length, leaf counting, leaf area, and the proportion of dry stuff.  The concentration of chlorophyll in the leaves, quantity of carbohydrates in the branches, fruit form parameters, average fruit weight, and overall yield. Proportion of dry matter in fruits and calculation of oil content. The interaction treatment, which included the application of 10 kg of cow dung per tree and the spraying of growing regulation by using dose of 20 mg L-1, significantly influenced the majority of those examined features